2006
DOI: 10.1303/aez.2006.269
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the contact sex pheromone of Gastrophysa atrocyanea (Coleoptera: Chrysomelidae)

Abstract: The mating behavior of the male Gastrophysa atrocyanea, that is, extrusion of the aedeagus, was elicited by the cuticular hydrocarbons on the surface of the female body. Males attempted to mate with a dummy treated with the female equivalent of the female elytra extracts. After fractionation of the elytra extracts by Florisil column chromatography and reverse phase high performance liquid chromatography, two fractions, consisting mainly of methylheptacosanes and methylnonacosanes were found to elicit the male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 15 publications
2
33
0
1
Order By: Relevance
“…Since the five phases of male behavior are conducted step by step, this mating sequence is considered to be behavior formulated with extremely high probability. Similar mating sequences were observed after encounters between males and females in several other Chrysomelidae: L. decemlineata 9,13,16 , G. atrocyanea 19 , and P. cochleariae 5 . When the male B. longissima attempted to mate, some females walked away.…”
Section: Mating Sequence In Brontispa Longissimasupporting
confidence: 65%
See 3 more Smart Citations
“…Since the five phases of male behavior are conducted step by step, this mating sequence is considered to be behavior formulated with extremely high probability. Similar mating sequences were observed after encounters between males and females in several other Chrysomelidae: L. decemlineata 9,13,16 , G. atrocyanea 19 , and P. cochleariae 5 . When the male B. longissima attempted to mate, some females walked away.…”
Section: Mating Sequence In Brontispa Longissimasupporting
confidence: 65%
“…Male contact with the antennae, tarsi, or palpi was considered to be involved in perception of female-specific cues. The importance of direct contact in mating behavior has been demonstrated in other Chrysomelidae: L. decemlineata 9,13,16 , G. atrocyanea 19 , C. cobaltinus 18 , and C. auratus 18 . However, more detailed examinations will be needed to determine the presence of attractant cues in the mating behavior of B. longissima.…”
Section: Mating Sequence In Brontispa Longissimamentioning
confidence: 96%
See 2 more Smart Citations
“…The non-polar CHCs have been extensively investigated over the past three decades with respect to their role as semiochemicals (Howard, 1993;Singer, 1998;Howard and Blomquist, 2005). A multitude of studies have shown that CHCs are not only involved in the diverse interactions of social insects (Greene and Gordon, 2003;Endler et al, 2004;van Zweden and d'Ettorre, 2010) but also used by many solitary insects as contact stimuli when searching for oviposition sites (Colazza et al, 2007;Rostas and Wolfling, 2009;Darrouzet et al, 2010) or sexual mates (Syvertsen et al, 1995;Sullivan, 2002;Steiner et al, 2005;Steiner et al, 2006;Sugeno et al, 2006;Geiselhardt et al, 2009;Ferveur and Cobb, 2010;Ginzel, 2010;Ruther et al, 2011).…”
Section: Introductionmentioning
confidence: 99%